Quality Improvement Management Based on Partnership and ICT Advantages - Efendi, Nafsir; Syamsudidin, Abin; Wasliman, Iim; Arifin, Daeng (EARR (Educational Administration Research and Review), 2021)
This study aims to analyze quality improvement management based on partnership and ICT advantages in multi case study at SMK Muhammadiyah 1 and SMK YPT 1 Purbalingga Regency. The research approach used is a qualitative survey with correlational analysis techniques. This correlational analysis technique is used to measure strategy towards knowledge of systems approach, the ability to empower approaches in quality improvement management. The results showed that Partnership-Based School Quality Improvement Program and ICT ExcellenceÂ  as it showed that the two SMKs had developed a partnership-based school quality improvement program and ICT excellence. The results of the research relate to the implementation of partnership-based school quality improvement programs and the excellence of ICT carried out by the two schools is fully under the control of the respective principals as the person in charge of the entire program so that in its implementation there is proper and directed coordination and control. The concept of a partnership-based school quality improvement program and ICT excellence that is expected by the school is that this program can run continuously and consistently and directed with all parties involved in this activity